MAKERS WEB SITE (WEB SITE) A & W COMPUTER WITH MICROSOFT FRONTPAGE 2000 - Mohammad Anwar Rosyid; Susi Wagiyati, Skom, MMSI Susi Wagiyati, Skom, MMSI (Jurnal Sistem Informasi, 2001)
Today's progress has touched all aspects of life. especially in terms of computer technology. In the world of computers is currently known by the term Internet. Almost all people, especially in cities - big cities never heard that term, and may well use them. Unfortunately not all internet users understand how to create web pages. because then that Internet users retrieve information more than providing information on when using the internet. For this reason the author hopes this PI can give an idea of designing a simple web site.